Implementasi Model Pembelajaran IPA dalam Meningkatkan Kemampuan Argumentasi Ilmiah Peserta Didik Jenjang Sekolah Menengah : Studi Kepustakaan - Syarful Annam (Lembaga Einstein College (LEC), 2026)
Argumentation skills are one of the main objectives of science learning because students who study science must know scientific explanations of natural phenomena, use them to solve problems and be able to understand other findings they obtain. This study is a Systematic Literature Review (SLR) that aims to identify and analyze the most effective learning models to improve students' scientific argumentation skills in science learning. This study was assisted by the Publish or Perish application to search for relevant research articles in the Google Scholar database using the keywords